If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y-12=30-6y
We move all terms to the left:
y-12-(30-6y)=0
We add all the numbers together, and all the variables
y-(-6y+30)-12=0
We get rid of parentheses
y+6y-30-12=0
We add all the numbers together, and all the variables
7y-42=0
We move all terms containing y to the left, all other terms to the right
7y=42
y=42/7
y=6
| 52x-(x+3)=7-x | | 3x+3=(x+1)*3 | | 4x2-12x+17=0 | | 3+3a=4 | | 6-8x=-90 | | 3+2a=11 | | (8x+5)=(4x+ | | 2x+19=10x+-45 | | 2x+18=10x-45 | | (X+5)(3X-4)-6(x2+2)+4=0 | | 6(3w+10)/4=2 | | 5m+11=23+3m | | 4(x+3)=2(x-9) | | 5x=13=-27-3x | | (c+3)(c-5)=0 | | s=3+3/5 | | 2y-3=7y-38 | | 25+95+x=180 | | 30/24=100/x | | 120+38+x=180 | | 25730=x/100 | | 10+20+x=180 | | 18-7m=30 | | 3x2−20x−7=0 | | 105+30+x=180 | | 39+75+x=180 | | 25+110+x=180 | | 38+120+x=180 | | 2)4x+3)=10x-2 | | 2(2l+9)=34 | | 1x=32+3/2 | | 8x+1=12x-17 |